Physiotherapy Management and Technology Use for Parkinson’s Disease: A Survey Among Greek Physiotherapists - Despoina Papageorgiou; Vasiliki Sakellari; George A. Koumantakis; Viktoria Gkoraki; Nikolaos Chrysagis (Applied Sciences)
The purpose of this study is to investigate Greek physical therapists’ perceptions of therapeutic approaches, assessment tools, and the use of technology in the treatment of Parkinson’s disease. A cross-sectional survey was conducted using an online questionnaire consisting of 26 questions. The questionnaire was addressed to Greek physiotherapists who were registered with the Panhellenic Physical Therapy Association (PPTA) at the time of the survey and practiced their profession in Greece. A total of 203 physical therapists who met the inclusion criteria participated in the study. Out of all the participants, 65% had over 10 years of work experience and treated 1–9 patients with PD per year. Additionally, 84.7% of participants communicated with health scientists as part of the interdisciplinary collaboration, and 23.2% used assessment tools/scales frequently. New technologies were only used by 24.6% of participants despite a positive view of their benefits (70.9%). Physiotherapists who attended a lifelong educational program or adult neurological physiotherapy seminars or held a master’s or doctoral degree in physiotherapy used new technologies at higher rates of 64% and 68%, respectively. Finally, the use of new technologies was related to the acquisition of a master’s degree or lifelong training specialization.